Applications and Comparison of Dimensionality Reduction Methods for Microbiome Data - Armstrong, George; Rahman, Gibraan; Martino, Cameron; McDonald, Daniel; Gonzalez, Antonio; Mishne, Gal; Knight, Rob (Frontiers in Bioinformatics, 2022)
Dimensionality reduction techniques are a key component of most microbiome studies, providing both the ability to tractably visualize complex microbiome datasets and the starting point for additional, more formal, statistical analyses. In this review, we discuss the motivation for applying dimensionality reduction techniques, the special characteristics of microbiome data such as sparsity and compositionality that make this difficult, the different categories of strategies that are available for dimensionality reduction, and examples from the literature of how they have been successfully applied (together with pitfalls to avoid). We conclude by describing the need for further development in the field, in particular combining the power of phylogenetic analysis with the ability to handle sparsity, compositionality, and non-normality, as well as discussing current techniques that should be applied more widely in future analyses.